Examining the influence of principal leadership, pedagogical, and professional competence on teacher performance in elementary schools: A multiple regression analysis - Nofvin Sundaryanti; Supriyoko Supriyoko (Journal of Education Policy and Management Studies, 2025)
Teacher performance is a crucial determinant of the quality of learning in elementary schools. This study aims to examine the influence of principal leadership, pedagogical competence, and professional competence on the performance of elementary school teachers. Employing a quantitative correlational design with multiple regression analysis, the study involved 87 teachers selected through random sampling from a population of 111 elementary school teachers in Ngawen District, Gunungkidul, Indonesia. Data were collected using structured questionnaires, and instrument validity and reliability were tested using Pearson’s Product Moment correlation and Cronbach’s Alpha. The findings reveal that principal leadership, pedagogical competence, and professional competence simultaneously have a significant effect on teacher performance (R² = 0.207, F = 7.235, p < 0.05). Partially, principal leadership (β = 0.355, p < 0.05) and pedagogical competence (β = 0.349, p < 0.05) show positive and significant effects on teacher performance, while professional competence indicates a significant but negative effect (β = –0.360, p < 0.05). These results suggest that improving principal leadership and pedagogical competence can enhance teacher performance, while the negative contribution of professional competence requires further exploration. The study provides practical implications for school leaders and policymakers in strengthening teacher development programs to improve the quality of education.